2019
DOI: 10.3847/1538-4357/ab21d0
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength Investigation of Pulsar Wind Nebula DA 495 with HAWC, VERITAS, and NuSTAR

Abstract: Pulsar Wind Nebula (PWN) DA 495 (G65.7+1.2) was detected in TeV gamma-rays by the High Altitude Water Cherenkov Observatory (HAWC) in 2017 (2HWC J1953+294). Follow-up observations by the Very Energetic Radiation Imaging Telescope Array System (VERITAS) confirmed the association between 2HWC J1953+294 and DA 495 and found the TeV emission to be spatially coincident with the radio emission first reported in 1968. The detection of TeV gamma-rays from DA 495, along with past X-ray detection up to 10 keV, prompted … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…There are also several middle-aged PWNe whose high-energy emission is not explained by a leptonic model alone. For example, NuSTAR observation of the evolved PWN DA 495 found that a hybrid SED model composed of both leptonic and hadronic components is required to account for the multi-wavelength SED [12].…”
Section: Pos(icrc2021)963mentioning
confidence: 99%
See 1 more Smart Citation
“…There are also several middle-aged PWNe whose high-energy emission is not explained by a leptonic model alone. For example, NuSTAR observation of the evolved PWN DA 495 found that a hybrid SED model composed of both leptonic and hadronic components is required to account for the multi-wavelength SED [12].…”
Section: Pos(icrc2021)963mentioning
confidence: 99%
“…We will jointly analyze available X-ray data from Chandra and XMM observations in order to maximize our capacity to characterize the broad-band X-ray morphology/spectra of PWNe. We largely follow the NuSTAR data analysis of other PWNe such as DA 495 [12]. Upon detecting a pulsation signal, we can remove photon events from the pulsed components using a folded lightcurve or extrapolate the pulsar's Chandra spectrum and estimate its contribution in the NuSTAR band -these are the standard methods for mitigating the contamination of the pulsar [5].…”
Section: Nustar Data Analysismentioning
confidence: 99%
“…We used a 90-ks NuSTAR observation (ObsID 30362002002) taken in 2017 June as a part of the NuSTAR-VERITAS-HAWC Legacy program which includes observations of PWN DA 495 (Coerver et al 2019) and the TeV gamma-ray binary HESS J0632+057 (Archer et al 2020), and two archival Chandra observations (ObsIDs 9081 and 22145) which were taken with 10 ks exposures in 2008 and 2019, respectively. We also considered a handful of Swift/XRT observations of the field, but their short exposures yielded only a few counts in each observation, and so the Swift data are not very useful even after combining all the data.…”
Section: X-ray Observations and Data Analysismentioning
confidence: 99%
“…However, the small ratio of W e /W p ∼ 0.01-0.03 is still difficult to reconcile with the p-p collision case since the total kinetic energy of secondary electrons (i.e. byproducts of charged pion decays) should be ∼ 1/3 of the total radiation energy of π 0 gamma-rays (Coerver et al 2019). In order to yield the ratio W e /W p comparable to ∼ 1/3, it requires a lower ambient B-field, which seems implausible within a molecular cloud where the B-field should be amplified.…”
Section: Hadronic Interactionsmentioning
confidence: 99%
“…The results of this analysis were originally reported on in Abeysekara et al (2018b) as part of a follow-up study on new TeV gamma-ray sources detected by HAWC, and the strong magnetic fields measured by study of the radio spectrum made the TeV detection unexpected (Kothes et al, 2008). Second, starting with Section 5.2, the entire text of a paper accepted for publication in the Astrophysical Journal, titled: "Multiwavelength Study of Pulsar Wind Nebula DA 495 with NuSTAR, VERITAS and HAWC," is included (Coerver et al, 2019).…”
Section: Chapter 5 Pwn Da 495 (2hwc J1953+294)mentioning
confidence: 99%